Co-localization of corticotropin-releasing factor and vesicular glutamate transporters within axon terminals of the rat dorsal raphe nucleus - Waselus, Maria (2007)
Electrophysiological, microdialysis and behavioral studies support a modulatory role for corticotropin-releasing factor (CRF) in regulating the dorsal raphe nucleus (DRN)-serotonin (5-HT) system. CRF and 5-HT are implicated in the pathophysiology of depression, thus neuroanatomical substrates of CRF-DRN-5-HT interactions are of interest. Identification of co-transmitters within DRN CRF axon terminals is important for elucidating the complex effects underlying CRF afferent regulation of DRN neurons. This study investigated whether CRF-labeled axon terminals within the DRN contain immunoreactivity for vesicular glutamate transporters (isoforms vGlut1 and vGlut2) indicative of the excitatory neurotransmitter glutamate. Dual immunohistochemistry for CRF and either vGlut1 or vGlut2 was conducted within the same tissue section and immunofluorescence results indicated patterns of immunoreactivity consistent with previous reports. Abundant vGlut1- and vGlut2-immunoreactivity was found in puncta exhibiting a largely uniform distribution, whereas CRF-immunoreactivity was localized to topographically distributed varicose processes within the DRN. Profiles containing both CRF- and either vGlut1- or vGlut2-immunoreactivity were apparent in the DRN. Electron microscopy confirmed that immunoreactivity for CRF and vGlut1 was localized primarily to separate axon terminals in the DRN, with a subset co-localizing CRF and vGlut1. Examination of CRF and vGlut2 immunoreactivities in the DRN indicated that CRF and vGlut2 were found within the same axon terminal more frequently than CRF and vGlut1. Overall, these anatomical findings suggest that CRF may function, in part, with the excitatory neurotransmitter glutamate in the modulation of neuronal activity in the DRN.